The classical three ways of the spiritual life and the interior knowledge of the ignatians Exercises - Lamarthée Estrade, SJ, Pablo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
This article explains how the dynamic of Interior knowledge within the Spiritual Exercises that is present during the four weeks of the spiritual process as envisioned by Ignatius corresponds to the classical three ways of spirituality. Thus internal knowledge of sins [63] is linked with the purgative way, inner knowledge of the Lord [104] with the illuminative way and interior knowledge of all good received [233] with the unitive way. Such a reading of the Exercises helps us to approach it not only as an Ignatian means of knowing oneself, God and the world, but opens us to the possibility of understanding it as a process with clear and well-organized steps. This bond between Interior knowledge of the Exercises and the traditional three ways will in turn allow us to highlight new aspects of the classical scheme from an Ignatian perspective.
Keywords: Spiritual exercises; spiritual growth; spiritual process; interior knowledge; union with God